Deaths in jail: a retrospective analysis of autopsies performed at the Legal Medicine Unit of Pavia (1999-2022) - Belli, Giacomo; Romão, Mateus E.; Lacquagni, Riccardo; Bertoglio, Barbara; Bertolotti, Andrea; Tamellini, Gaia; Morini, Luca; Javan, Gulnaz T.; Setti, Ilaria; Visonà, Silvia D. (Frontiers in Psychiatry, 2024)
Introduction The high rate of incarceration, now exceeding 11.5 million people worldwide, has raised concerns about the conditions within penal institutions, such as the consequences of incarceration on the person. This retrospective study aims to investigate the issue of death in custody, exploring the relationship between incarceration, health vulnerabilities, and death from the forensic pathologist’s point of view. Methods We analyzed, from a forensic, clinical and toxicological perspective, 86 cases of deaths in detention facilities in North-Western Italy from 1999 to 2022. Results The analysis has shown that suicide, mainly committed by hanging, plastic bag suffocation and butane intoxication, represents the leading type of violent death (52%), followed by accidental deaths (16%). On the other hand, cardiovascular diseases are the leading cause of natural deaths (42%), followed by infectious diseases (especially HIV-related). Discussion The present study identifies the most frequent and critical situations and risk factors related to death in custody and the profile of the inmate who is at a higher risk of death, allowing to highlight the issues to be addressed from a public health point of view. On the whole, it calls for comprehensive reforms, aligned with international human rights standards, addressing mental and physical care gaps, improving correctional officers' education, and training, and focusing on rehabilitation with well-being and dignity.